The Role of Interpersonal Intelligence in Vocabulary Retention Via Peer Tutoring: A Quasi-Experimental Study with Haider Belkacem Middle School Learners, Sidi Aissa, M’sila - Bouazza Ali; Mezilekh Abderraouf (UNIVERSITÉ MOHAMED BOUDIAF - M’SILA, 2025)
It is of paramount importance for middle school EFL learners to retain vocabulary. This research examines the influence of interpersonal intelligence on the retention of language during peer tutoring sessions. Skills associated with interpersonal intelligence, such as collaboration, communication, and support, are crucial for the success of socially-driven peer tutoring. A quasi-experimental study conducted at Haider Belkacem Middle School in Sidi Aissa, M'sila, involved one group receiving peer tutoring while another group was subjected to teacher-led sessions. The structured peer tutoring sessions comprised interactive assignments, collaborative learning, and reciprocal feedback over a span of six weeks, aimed at enhancing vocabulary acquisition in the experimental group. The assessment of short-term improvement and long-term retention was conducted through vocabulary pre-tests and delayed post-tests. The findings indicated that peer tutoring significantly boosted language memory within the experimental group, which attained an average score of 11.88 in contrast to 9.59. Qualitative research suggests that interpersonal intelligence serves to raise learner motivation, engagement, as well as social and communicative competencies. This study substantiates the notion that peer tutoring not only enhances vocabulary retention but also fosters interpersonal skills in English as a Foreign Language (EFL) environments, thereby advocating for its incorporation into middle school language curricula.
Keywords: interpersonal intelligence; vocabulary retention; peer tutoring; EFL; middle school learners; quasi-experimental study